Imigração árabe e religiosidade em São José do Rio Preto: Igreja Católica Apostólica Ortodoxa Antioquina : um estudo de caso - Martins, Daniel Maia (2010)
The present research is a case study that has as a goal the study of the Antiochin Orthodox Apostolic Catholic Church in São José do Rio Preto and the immigration of the Syrian-Lebanese to this particular town. Mistaken by Muslims and/or Turkish, the first Syrian-Lebanese to arrive in Brazil were Christians. In São José do Rio Preto, many of them were Orthodox Christian. The context of their mother land in the end of the 19th century, beginning of the 20th and history about their journey to America are presented in this research as well as the beginning of the Antiochin Orthodox Apostolic Catholic Church in São José do Rio Preto. In order to do so, historical documents were used as well as testimonials and literature. The research also dealt with theological and liturgical factors of this church, which came from several interviews - with priests, church goers, Syrian-lebanese descendents, immigrants and researchers - and from participant observation. It is expected from this research to contribute with the studies of the Brazilian religious context and Religion science.